Cytotoxicity of polymethylmethacrylate copolymers (Annals of Medical Research, 2021)
Aim: This study aimed to determine the cytotoxicity of polymethylmethacrylate copolymers.Material and Methods: The polymethylmethacrylate resin was used to fabricate the samples. Ethyl-methacrylate, butyl-methacrylate and isobutyl-methacrylate, were used to form the copolymerization of polymethylmethacrylate. 10%-20%-30%-40% ethyl-methacrylate, butyl-methacrylate and isobutyl-methacrylate monomers were added to the methyl-methacrylate, which is the monomer of the control group, and 13 different groups were formed. Five specimens (n=5) for cytotoxicity test were prepared for each group. Cytotoxicity effects of the resins at 24th and 48th hours were evaluated by MTT assay. The data of the cytotoxicity test was analyzed by applying one-way variance analysis.Results: The effect of monomer type and monomer percent on cell viability was significant in both periods (p 0.01). The percentage of cell viability of all groups at both times was over 90%. The cell viability showed a tendency to decrease by increasing the percentage of monomer added in both periods. The highest and lowest cell viability in 24th hours were observed in 10% ethyl-methacrylate and 30% butyl-methacrylate groups respectively, while the highest and lowest cell viability in a 48th hour was observed in 10% butyl-methacrylate and 40% butyl-methacrylate groups, respectively.Conclusion: The cytotoxic effects of copolymer resins were not observed at 24th and 48th hours. Cell viability was found at more than 90% in both periods. It was shown that the copolymer resins formed by the addition of 10%, 20%, 30%, and 40% by volume of isobutyl-methacrylate, butyl-methacrylate, and ethyl-methacrylate to the methyl-methacrylate were biocompatible materials.Keywords: Acrylic resins; cell survival; cytotoxicity tests, immunologic; denture bases; polymers.
Keywords: Acrylic resins; cell survival; cytotoxicity tests, immunologic; denture bases; polymers.